INVASIVE LOBULAR CARCINOMAS TREATED AT HOSPITAL DE CLÍNICAS OF UFPR: INCIDENCE, CHARACTERISTICS AND CLINICAL OUTCOME - Gasperin, Anaí Caroline Hamann; Romaniello, Gabriela; Furuie, Isabella Naomi; Mauro, Maria Júlia Jorge; Melo, Thayane Guimarães de; Gasperin Júnior, Plínio; Budel, Vinicius Milani (Mastology, 2018)
Objective: The aim of this study is to depict the clinical and epidemiological profile of patients treated for invasive lobular carcinoma (ILC) at Hospital das Clínicas of Universidade Federal do Paraná (HC-UFPR) over the course of ten years and to evaluate the variation of ILC dimensions on imaging exams by comparing them to real-size lesions identified in surgical specimens. Methods: Patients undergoing breast surgical procedures at HC-UFPR from 2005 to 2014 were selected. Out of these, 36 were diagnosed with ILC and had their medical files sought after clinical, epidemiological, therapeutic and prognosis characteristics. The variance of tumor sizes in imaging methods and anatomopathological descriptions were also studied. Results: Patients’ mean age at diagnosis was 59.6 years. Most of them were classified as clinical stages II (40%) and III (26.7%) by the time they were diagnosed. The majority of tumors were HER2 negative (77.2%) and estrogen-receptor positive (90%). The surgical treatment was radical in 74.2% of the cases. 31.4% of the patients underwent both mammography and ultrasonography screening and 45.7% underwent only one of them. None of the patients were submitted to magnetic resonance imaging (MRI). Conclusion: Data found about patients with invasive lobular carcinoma at HC-UFPR is in accordance with the medical literature, including incidence rates and tumor characteristics. The variance of tumor sizes in imaging exams and surgical specimen was not statistically significant.